SPECT/CT in Postoperative Foot and Ankle Pain - Kampen, Willm Uwe; Westphal, Florian; Van Den Wyngaert, Tim; Strobel, Klaus; Kuwert, Torsten; Van Der Bruggen, Wouter; Gnanasegaran, Gopinath; Jens, Jan-Hauke; Paycha, Frederic (Seminars in Nuclear Medicine, 2018)
Postoperative pain is a clinically relevant issue in orthopedic patients, affecting more than 40% 1 year after foot and ankle surgery. Because of the very complex anatomy with many different joints and several motion axes, clinical examination and conventional imaging are sometimes not sufficient to identify a local pain generator. Local uptake of bone-seeking radiopharmaceuticals is known to correlate accurately with sites of pain generating foci and, thus, bone scintigraphy has been an established method to evaluate these respective patients for many years. However, the specificity is rather low if only planar images are acquired. The development of SPECT and especially of hybrid SPECT and CT imaging has significantly enhanced the specificity of this technique. The combination of both functional and morphological imaging, ideally performed with a dedicated SPECT/CT system to minimize misregistration owing to motion artifacts and to enhance image quality by attenuation correction, allows an early and reliable detection of pathologic bone processes, even in patients where radiological imaging with MRI or CT is hampered by metal implants. In diabetic patients with a neuropathic Charcot osteoarthropathy, infection can be differentiated from inflammatory bone alterations (causing bone marrow edema) almost certainly using SPECT/CT with radiolabeled white blood cells and antigranulocyte antibodies, allowing an individual and precise treatment planning either in the initial course of the disease or even after surgery. This article reviews the most frequent clinical challenges in patients after foot and ankle surgery, including a description of the various surgical procedures, the different imaging options with their advantages and disadvantages, and aims to integrate bone SPECT/CT into the clinical diagnostic workup.
EVALuna2:212298